O serviço social na luta contra a precarização do Sistema Único de Assistência Social em Sergipe : uma análise do acirramento dos desmontes de 2016 a 2020 - Correia, Miriam Santos Prescinca (2021)
This master's thesis entitled "Social Service in the Fight Against Precariousness of the Unified Social Assistance System in Sergipe: an analysis of the intensification of dismounting from 2016 to 2020" investigates the role of Social Service, through the CFESS-CRESS set and its articulations with social movements and other categories, in their struggles to defend the Unified Social Assistance System (SUAS) in the state of Sergipe. To this end, the period 2016-2020 was delimited, with the main milestones being the coup that ousted then-president Dilma Rousseff and the subsequent implementation of Constitutional Amendment No. 95 or "Law of Ceiling of Spending" by ultra neoliberal governments that were succeeded (TemerBolsonaro). These were the two main recent events, in the political-economic aspect, which marked a period of deepening precariousness and dismantling of social rights, which has been taking place since the 1990s and has intensified in the last decade. As a higher-level profession, Social Work brings in its genesis the movement intertwined with the stage of monopoly capitalism in Brazil and which, from the critical perspective adopted in its professional project, started to act on the expressions of the social issue through the elaboration and Execution of Social Policies, including Social Assistance. Therefore, the social worker is challenged with an intervention committed to the materialization of SUAS, towards its advancement, strengthening and resistance. It was, therefore, with the purpose of mapping the strategic actions of the professional category over the last five years, that this dissertation was configured. In this sense, we assume that the ethical-political dimension that guides Social Work professionals is based on their strategies of resistance to the dismantling of social achievements in the face of recent government attacks on the social pact, reaffirming the current direction of the profession in defense of universal right (BEHRING; BOSCHETTI 2010). To conduct this research, within the due scientific rigor, the historical-dialectical materialist approach was adopted, under which the object is apprehended in its complex movement and the syntheses of multiple determinations of concrete reality (KOSIK, 2006). Therefore, this work was carried out as a documental and bibliographic research, qualitative in nature, under the ontological perspective of knowledge, which we proposed to understand, beyond the appearance of reality, the essence of the totality of social life (NETTO, 2009 ). Among the results obtained in the course of the investigation carried out, we could consider that the struggles in defense of the SUAS materiality in the direction of universalization have enabled the resumption of the debate that brings them even closer to the ethical-political dimension of the professional project of the s Brazilian social workers. It was also noticed an intensification of activities carried out by the CFESS-CRESS group aimed at the defense of Social Security and SUAS, raising banners such as: "No to cuts to Social Security and SUAS"; "No rights less"; "SUAS Resist" and others. In addition, the category has positioned itself with social movements and representatives of SUAS Workers to join forces in mobilizing against the attacks that the Assistance Policy has been suffering in the last five years.